SOCIAL CONFLICT IN THE PERFORMANCE PATRI THEATRE “SEMAR MENCARI RAGA (STUDY OF LITERARY SOCIOLOGY) - Maulana, Achmad Buchory (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
The research journal entitled "Social Conflict in the Patri Theatre Performance 'Semar Mencari Raga' (Sociological Study of Literature)" aims to describe the various factors behind a social conflict and the types of social conflicts contained in the performance of Teater Patri with the play Semar Mencari Raga. This research is a type of descriptive qualitative research with observational analysis techniques. The subject is a sentence that contains various factors behind a social conflict and the types of social conflicts contained in the performance of Teater Patri with the play Semar Mencari Raga, while the object is dialogue and words of introduction to the dialogue contained in the performance of Teater Patri with the play Semar Mencari Raga. The results of this study, found 21 data describing the factors causing conflict and its types. These are classified into: characteristics that differ from each other (4 data), occurrence of poverty disparity (4 data), inclusive characteristics and behaviors (2 data), latent conflict (3 data), manifest conflict (5 data), and conflict on the surface (3 data).